The Pandemic Era of COVID-19: Reflection on The Regional Government Budget Sustainability for The Optimism of National Economic Recovery - Suwanda, Dadang (Journal of Ecohumanism, 2024)
During the COVID-19 pandemic, many local governments experienced economic disruption as businesses closed or scaled back operations, unemployment rose, and government revenues decreased. This led to budget challenges for local governments as they worked to address the needs of their communities and support economic recovery efforts. Therefore, local governments should prioritize funding for healthcare, social services, economic recovery initiatives, and infrastructure projects in their budgets during the COVID-19 pandemic in order to support the national economy recovery and address the needs of their communities. The government decided that the village funds budget could be used for a wide range of things, such as giving money directly to the village's poor and working to combat the COVID-19 pandemic. The purpose of this study is to determine the extent to which local governments' budget structures prioritized managing the COVID-19 pandemic in the region to deal with consequences in the form of threats to the national economic system and financial system stability, with a particular emphasis on health spending, social safety nets, and economic recovery. The technique used qualitative research conducted through a document look at (desk studies). The data is sourced from secondary information in developmen t plans files, central government budgets, local government budgets, and amendments. The data was obtained through direct access to government websites, particularly the COVID-19 task force website, the Ministry of Finance website and the Ministry of Home Affairs website. The findings indicate that the COVID-19 pandemic in Indonesia has significantly impacted the country's economy and socio-economic situation since the second quarter of 2021. People's purchasing power is going down, unemployment is going up, and poverty will worsen. These are all current and future government problems. The implications and recommendations of the findings of this study are explained further.